ISOcat: remodelling metadata for language resources. (11th November 2009) - Kemps-Snijders, Marc; Windhouwer, Menzo; Wittenburg, Peter; Wright, Sue Ellen
The Max Planck Institute for Psycholinguistics in Nijmegen, The Netherlands, is creating a state-of-the-art web environment for the ISO TC 37 (terminology and other language and content resources) metadata registry. This Data Category Registry (DCR) is called ISOcat and encompasses data categories for a broad range of language resources. Under the governance of the DCR Board, ISOcat provides an open work space for creating data category specifications, defining Data Category Selections (DCSs) (domain-specific groups of data categories), and standardising selected data categories and DCSs. Designers visualise future interactivity among the DCR, reference registries and ontological knowledge spaces.